Investigation of effects and parameter interactions in metal microforming processes - Eichenhüller, Bernd; Engel, Ulf (4M/ICOMM 2009, Proc. Global Conf on Micro Manufacture (incorp. 5th Int. Conf. on Multi-Material Micro Manufacture 4M and 4th Int. Conf. on Micro Manufacturing ICOMM), 2009)
The occurrence of size effects while miniaturising forming processes from macro to micro scale is a well known fact. Numerous research activities were established worldwide to identify and qualify these size effects and a number of models were developed in order to describe and explain the investigated behaviour. In doing so, several process parameters were found to have a strong influence on the forming behaviour, but almost exclusively the influence of single isolated parameters was investigated. This paper is focusing on parameter interactions of relevant process factors, regarding their influence on the forming behaviour. It will be shown that the process result of multiple parameter changes is not simply the accumulation of each individual parameter change. The experimental research is done using a full backward extrusion process to extrude a single form feature. In a first series of experiments an axial symmetrical pin was formed. Based on this investigation a more complex geometry, a rectangular fin is extruded. The effects and interactions of parameter changes - investigated parameters are the temperature, the size of the form feature, lubrication, grain size and velocity - can be observed in the development of the aspect ratio, defined as ratio between feature height and width or diameter of the feature.
LFT Import::2019-08-05 (316)
Keywords: Extrusion; Microforming; Parameter interaction; Size effect